Evaluation of apricot genotypes for table use, drying and their storage life - SINGH, D B; KUMAR, DINESH; AHMED, NAZEER (The Indian Journal of Agricultural Sciences, 2016)
Fifteen apricot (Prunus armeniaca L.) varieties/genotypes grown under temperate ecosystem were evaluated for table use, drying, quality maintenance and shelf life during their storage at refrigerated temperature (60% RH and 4±2°C Temp.). Storage life of fresh fruit PLW, TSS, acidity, ascorbic acid was measured in stored fruits at 4 days interval till 28 days of storage. Present investigations revealed that there were significant differences for physico chemical characteristics of different apricot varieties/genotypes, their drying potential and quality maintenance during storage period. The varieties CITH-AP-1, CITH-AP-2, CITH-AP-6, Heartly, Turkey and New Castle were better with respect to quality parameters like weight, size, firmness, TSS, TSS/acid ratio, ascorbic acid and b-carotene and maximum shelf life, whereas, after drying varieties such as CITH-AP-2, CITH-AP-3, Afghani, Turkey and Erani were having good quality characteristics like colour, firmness, TSS, ascorbic acid, b-carotene and better shelf life. These varieties need further exploitation for commercialization and significantly high returns.